Voluntarios en una guerra de tinta y papel: los voluntarios españoles de la Primera Guerra Mundial en la prensa - Alejandro Acosta López (Cahiers de Civilisation Espagnole Contemporaine)
In neutral Spain in 1914-1918, numerous polemics fuelled the conflict between Alliedophiles and Germanophiles in the pages of the press. One of the aspects that served to air the different opinions of intellectuals and journalists attached to the different camps was the presence of a contingent of Spaniards who had enlisted as volunteers in the ranks of the French Foreign Legion. The aim of this article is to examine the view of these Spanish volunteers in the Allied and Germanophile press from a comparative perspective, in order to observe the different resources and strategies deployed to praise or denigrate the phenomenon of voluntary service, an entelechy of the timid Spanish interventionism and a phenomenon in which the Allied groups placed their desire for foreign projection. Likewise, the influence of foreign propaganda strategies and the role played by foreign services in the strengthening of the discourse on volunteers is also assessed, which can help us to better understand the needs of the Spanish press and the ways of doing journalism in the period.